WORK POSTURE RELATIONS WITH LOW BACK PAIN COMPLAINT ON PARTNERS PART OF PT 'X' MANUFACTURE OF TOBACCO PRODUCTS - Suryadi, Iwan; Rachmawati, Siti (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Backgroud: Non-ergonomic work posture at work will risk the occurrence of occupational diseases and occupational accidents. One complaint due to work is low back pain (LBP) which is a pain that is felt on the lower back. Purpose: To determine the relationship of work posture with subjective complaints low back pain at PT X. Method: Research method is analytic with cross sectional research design. Sampling was done with total sampling of 53 samples. Assessment of work posture with rapid entire body assessment (REBA) method and subjective subjective complaints assessment of low back pain using modified questionnaire oswestry low back pain disability. Statistical test used spearman correlation test. The frequency distribution of job posture assessment with reba method is 35 respondents have medium value and 10 has high value, while for low back pain complaint there are 36 respondents who have severe crippled disability category. Result: The results showed there was a significant relationship between posture work with low back pain complaints with p value = 0.047 and r = 0.282. Conclusion: From the work posture assessment that for workers who have medium and high risk Reba for immediate action such as repair of work stations and providing understanding of ergonomic work positions.